The Impact of Law On Private Company in The Perspective of Mandatory Enterprise Registration (Wajib Daftar Perusahaan) In Pekanbaru City - Yeni Triana (Human Sustainability Procedia, 2018)
The common problem of micro and macro levels of business is the implementation of Mandatory Enterprise Registration as the consequence of lack of Law knowledge. Such a situation has raised certain issues of neglecting the regulations of Enterprise Registration. The present study aimed to analyze the enforcement of Mandatory Enterprise Registration for the micro and macro levels businesses in Labuh Baru Barat, Pekanbaru. The research method used in the present study was the sociology of Law study in which the study focused on the problems of Law and the practice in the society. It was field research in which the researcher conducted the study directly in the field. The study found that the Mandatory Enterprise Registration in the area of Pekanbaru was still under no condition. The majority of business owners had lack of Law knowledge and tend to neglect the regulations. The findings showed that the business owners had minimum knowledge of Enterprise Registration. It could be concluded that the Mandatory Enterprise Registration of the owners of micro and macro levels businesses in Pekanbaru needs to be a serious concern from the government agencies to expect they have good knowledge on enterprise registration. For the recommendations, the campaign should be sustained to promote the enterprise registration especially for the micro and macro business levels. The output of the enterprise registration is essential in the business competitions. Therefore, the follow-up actions of the present study are expected to give contributions to the researcher and the small and middle-level business owners, especially for the enterprise registration. This article is also can be taken as students’ object in studying the small and middle-level businesses in Pekanbaru.